Integrasi Teknologi Digital dalam Pengembangan Sistem Akuntansi Modern - Putri Salsabila; Agus Arwani (STAI Nurul Islam Mojokerto, 2025)
This study aims to systematically examine how digital technologies are integrated into modern accounting systems in Indonesia. Using a Systematic Literature Review (SLR) method, ten national journal articles from 2018–2023 were analyzed to identify trends, benefits, and challenges of technologies such as cloud accounting, artificial intelligence, big data, blockchain, and ERP. Findings show that digital integration enhances efficiency, accuracy, and transparency in financial reporting. However, barriers such as limited digital literacy, insufficient infrastructure, and inconsistent regulations hinder widespread adoption. The role of accountants is also evolving towards strategic data analysis. The study concludes that collaborative efforts among government, academia, and industry are essential for successful digital transformation in accounting. This research provides comprehensive insights and recommendations to support policy formulation and the development of technology-based accounting practices.